Quality of Public Space Safety at Kumbasari Tukad Badung Park, Denpasar - Eka Kartika Putra, Gde; Widiastuti, Widiastuti; Ketut Agusintadewi, Ni (Universitas Ibn Khaldun Bogor, 2022)
Public space / public space is a container that accommodates certain activities of the community both individually and in groups. Public space is stated to be ideal and must have several important aspects, namely convivial, namely comfortable, safe, then becomes a forum for the community to interact between fellow users or other individuals. One of the public spaces owned by the city of Denpasar is Taman Kumbasari Tukad Badung, Taman Kumbasari Tukad Badung is located on the edge along the Badung river which has a length of approximately 548 meters, is in the middle of Badung Market and Kumbasari market and is located on the banks of the Badung River. This location poses a risk to the safety of its users, especially during the rainy season. The purpose of this study is to determine the level of security at the Kumbasari Tukad Badung Park facilities considering the position of this public space is on the edge of the Tukad Badung River. References. The research method uses quantitative statistical methods, namely by giving values based on existing standards. The results showed that the percentage of the quality of public space security in Taman Kumbasari Tukad Badung is in the range of 50%, where the facilities in Kumbasari Park can be said to have standard public space security.